(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Polymerase chain reaction (PCR) is an experimental method in molecular biology that can achieve significant increases in small concentrations of certain nucleic acid (NA) fragments in biological material.